In reply - Rümenapf, Gerhard; Morbach, Stephan; Schmidt, Andrej; Sigl, Martin (Deutsches Ärzteblatt, 2020)
We would like to thank all of our colleagues for their valuable contributions to our work (1). There is obviously a consensus that structured, supervised exercise training (SET) is a valuable treatment measure with high evidence for suitable PAD...
Erwiderung zu Briefen an den Editor zu: Intermittent claudication and Asymptomatic Peripheral Arterial Disease Conservative treatment versus revascularization by Prof. Dr. med. Gerhard Rümenapf, Dr. med. Stephan Morbach, PD Dr. med. Andrej Schmidt, and Dr. med. Martin Sigl in issue 11/2020
Gesehen am 21.03.2025